POLITENESS STRATEGY ANALYSIS USED BY TENGGO WICAKSONO IN HIS YOUTUBE CHANNEL - Suryana, Yayan; Zahra, Siti Dhea Alfi; Asikin, Nida Amalia (Universitas Kuningan, 2023)
This study explores the politeness strategies employed by Tenggo Wicaksono in his Ome TV interactions on YouTube, focusing on their adaptation to informal, cross-cultural digital communication. Using a descriptive qualitative approach, 127 instances of politeness strategies were identified and analyzed based on Brown and Levinson’s framework, revealing a preference for positive politeness strategies (48%), followed by negative politeness (25%), bald on record (22%), and off-record (5%). Positive politeness strategies were prominently used to reduce social distance and build rapport, while negative politeness mitigated impositions in interactions involving greater social distance. The findings emphasize the importance of context and sociological variables, such as power dynamics and rank of imposition, in shaping linguistic choices. This research highlights the adaptability of politeness strategies in digital spaces and recommends further studies on their application across platforms and cultural contexts, providing valuable insights for digital content creators and educators navigating multicultural interactions. Keywords: Politeness strategies; Ome TV; digital communication; cross-cultural interaction; qualitative analysis; pragmatics.